TAP YAW TRADITIONAL MUSIC CULTURE NAKHON SI THAMMARAT - ลาดทุ่ง, ภูวนาถ (JOURNAL OF HUMANITIES AND SOCIAL SCIENCES SONGKHLA RAJABHAT UNIVERSITY, 2021)
Thap Yaw band, there is the hypothesis that this had received the influence from foreigners who had come to trade with the people in Nakhon Si Thammarat Province since the ancient time. By this had determined to be 3 periods as follows; 1st period, this was happened before 1907. There was mixing of Thap Yaw band but this won’t have the fixed form. Villages would bring Thap Yaw to play the music with orchestra in the parade in other traditions. 2nd period, this was the changing era from 1907 to 2002. There was playing Thap Yawwhich would hold the former form. For using Thap Yaw band to play the music with orchestra in the traditional parade, 10th month of ten month tradition, the original fabric that made up the parade by unison, Buddhist lent candle parade, offering robes to Buddhist priests at monastery parade, Naga parade or Naga ordination, marriage ceremony, Mahachat international events, etc. From this study, this was found that in this period, there was bringing of the flute, the treble fiddle, the Yi fiddle to play the music for making the rhythm for Thap Yaw band for increasing more interesting. 3rd period, the developing era from 2002 to the current situation. After this had developed more continuously. Thap Yaw band had the role on Nakhon Si Thammarat Province in other many festivals and there was setting of the Thap Yawcompetition in every year. There was playing Thap Yawin the applied for more. There was bringing of the keyboard, the guitar, the electric bass or other more international music instruments to mix perfectly. For the characteristic of Thap Yaw, this would be made with the real wood. There was popular to use the jackfruit wood due to this had the light weight. The wood body had the length approximately from 16 to 17 inches There was the front of Thap Yaw which had the width from 6 to 12 inches, the bottom of Thap Yaw which had the width approximately from 3 to 4 inches. This would be enhanced out liked the glass cup for using in the floor set for one-page leathering with the cow leather or the goat leather, etc.